Public Official Associations and State and Local Government: A Bridge Across One Hundred Years - Arnold, David S.; Plant, Jeremy F. (University Press Copublishing Division, 1994)
This volume is an authoritative description of a little-recognized element of modern governance: associations of public officials in state and local government. These associations, whose membership consists of elected and appointed officials such as mayors, legislators, council members, city and county managers, and planners, play an often overlooked role in public administration and governmental policy on state and local levels. This work provides an incisive analysis of their role using a combination of documentary sources and extensive personal interviews with a special interest in association management. It traces the historical development of associations from 1890 to 1990 within the context of the Progressive Movement, the New Deal, the Great Society, and the era of cutbacks and devolution. In addition, an examination of the effects of associations in the evolving administrative state touches upon many of the most important topics in public administration, including intergovernmental relations, by professionalism, ethics, and leadership. The text is augmented by an appendix of association profiles, an annotated bibliography, and an index.